Black halogen-free resin composition, prepreg, metal foil-coated laminated board and printed circuit board
By using a black halogen-free resin composition that controls the pH and Na ion content of black silica and epoxy resin, the existing black copper clad plate has been solved, and the high-performance black copper clad plate is achieved.
Patent Information
- Application Number
- CN202411974040.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
With the increasing demand for signal transmission, the existing black copper clad plate is difficult to meet the demand for improving the electrical performance of the board, and traditional black colorants have problems such as poor conductivity, reduced heat resistance and environmental pollution.
The dielectric properties and heat resistance of the sheet are optimized by controlling the proportion and treatment of components by controlling the proportion and treatment of the components.
It improves the high temperature and high frequency (CAF) and dielectric properties of the sheet, maintains excellent insulation performance, heat resistance and low thermal expansion coefficient, and improves the reliability and efficiency of signal transmission.
Smart Images

Figure BDA0005220031480000041 
Figure BDA0005220031480000042 
Figure BDA0005220031480000043
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laminated boards, and relates to a black halogen-free resin composition, a prepreg, a metal foil-clad laminated board and a printed circuit board. Background Art
[0002] Black circuit boards are not only aesthetically pleasing, but also have excellent thermal stability and light shielding properties. They are widely used in high-end mobile phones, tablet computers, game consoles and other electronic devices. With the development of electronic technology, the terminal's demand for signal transmission of black circuit boards is constantly increasing. With the continuous upgrading of electronic products, circuit boards are also constantly promoting their miniaturization, high density and high reliability. This makes the application of circuit boards in electronic devices more extensive and efficient, and the application scope of black circuit boards is also expanding.
[0003] At present, the commonly used black colorants for copper clad laminates include aniline black, carbon black, titanium black, black silica, etc. Carbon black and titanium black have poor insulation properties for copper clad laminates prepared from them due to their conductivity; aniline black has excellent insulation properties, but after being added, it will make the heat resistance of the board worse, and it contains chromium elements, which will cause environmental pollution; CN118125458B provides a black silica synthesized by calcining silane, which solves the problem of traditional carbon black powder floating easily during processing, causing environmental pollution and safety hazards to operators. Although the conductivity and dispersion problems of black colorants have been solved, with the continuous improvement of signal transmission needs in modern society, the requirements for the electrical properties of the board are also constantly increasing, so it is necessary to find materials that can bring better performance. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a black halogen-free resin composition, a prepreg, a metal foil-clad laminate and a printed circuit board.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a black halogen-free resin composition, wherein the black halogen-free resin composition comprises the following components in parts by weight:
[0007] (A) Epoxy resin: 100 parts
[0008] (B) Black silica: 10-30 parts
[0009] (C) Low dielectric curing agent: 30-100 parts
[0010] The black silica has a pH of 6-8 (e.g., 6, 6.2, 6.5, 6.8, 7.0, 7.3, 7.5, 7.7, 7.9 or 8), and a sodium ion content of ≤300 ppm (e.g., 0 ppm, 50 ppm, 120 ppm, 160 ppm, 180 ppm, 230 ppm, 260 ppm, 290 ppm or 300 ppm).
[0011] In the present invention, by controlling the pH and Na ion content of black silica, the influence of acidic substances and ion conductors in the black silica on the dielectric loss and the influence of alkaline substances on the moisture and heat resistance of the board are reduced, the influence of ion polarization and ion migration on the CAF resistance and dielectric properties of the copper clad board is reduced, the interface polarization effect of the matrix material is reduced, and the moisture absorption rate of the board is reduced; the cured product has excellent CAF resistance and low dielectric loss, and maintains excellent insulation performance, heat resistance and low thermal expansion coefficient. At the same time, the black silica also has excellent fluidity, dispersibility and light shielding effect.
[0012] Preferably, the black silicon dioxide is treated with a silane surface treatment agent.
[0013] Preferably, the silane-based surface treatment agent is selected from isocyanate-based surface treatment agents.
[0014] Preferably, the particle size distribution D50 of the black silica is 1-5 μm (e.g., 1 μm, 1.8 μm, 2.1 μm, 2.5 μm, 3.2 μm, 3.8 μm, 4.4 μm or 5 μm), and D100 is 7-12 μm (e.g., 7 μm, 7.8 μm, 8.6 μm, 9.2 μm, 10.1 μm, 11.2 μm or 12 μm).
[0015] In the present invention, relative to 100 parts by weight of epoxy resin, the content of the black silica is 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight, 23 parts by weight, 25 parts by weight, 27 parts by weight, 29 parts by weight or 30 parts by weight.
[0016] In the present invention, the epoxy resin is selected from any one of a bifunctional epoxy resin or a multifunctional epoxy resin or a combination of at least two thereof.
[0017] Preferably, the epoxy resin is selected from any one or a combination of at least two of dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethyl biphenyl epoxy resin, biphenyl epoxy resin, novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, epoxy resin containing C1-C6 alkyl, MDI modified epoxy resin, epoxy resin containing naphthalene ring or epoxidized polybutadiene.
[0018] Preferably, the epoxy equivalent of the epoxy resin is 100 to 600 g / eq, for example, 100 g / eq, 150 g / eq, 200 g / eq, 250 g / eq, 300 g / eq, 350 g / eq, 400 g / eq, 450 g / eq, 500 g / eq, 550 g / eq or 600 g / eq.
[0019] The low dielectric curing agent of the present invention is selected from one or a combination of at least two of an amine curing agent, a cyanate curing agent, an active ester curing agent, an anhydride curing agent or a maleimide curing agent.
[0020] In the present invention, relative to 100 parts by weight of epoxy resin, the content of low dielectric curing agent is 20 parts by weight, 24 parts by weight, 30 parts by weight, 36 parts by weight, 40 parts by weight, 43 parts by weight, 49 parts by weight, 51 parts by weight, 58 parts by weight, 66 parts by weight, 71 parts by weight, 75 parts by weight, 83 parts by weight, 86 parts by weight, 90 parts by weight, 94 parts by weight or 100 parts by weight. The use of low dielectric curing agent can further optimize the dielectric properties of the board and improve signal integrity, but excessive use of non-polar molecules will lead to apparent defects such as lack of resin, affecting the wettability and reliability of the board.
[0021] Preferably, the anhydride curing agent is selected from any one or a combination of at least two of the following formula I or formula II:
[0022]
[0023] Among them, n:x=1:1~8:1 (for example, 1:1, 2:1, 3:1, 5:1, 7:1 or 8:1).
[0024] Formula II is a copolymer resin having a structural unit derived from an aromatic vinyl compound and a structural unit derived from maleic anhydride.
[0025] Preferably, the active ester curing agent is selected from any one or a combination of at least two of the active esters having the following structure of Formula III or Formula IV:
[0026]
[0027] In III, X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25 (e.g., 0.25, 0.35, 0.40, 0.50, 0.55, 0.70, 0.80, 0.95, 1.15 or 1.25).
[0028]
[0029] In IV, m, n, and q are independently integers of 1 to 6 (e.g., 1, 2, 3, 4, 5, or 6), X is phenyl or naphthyl, and Y is the following group:
[0030]
[0031] Where K is 0 or 1.
[0032] Preferably, the low dielectric curing agent includes an active ester curing agent, and the content of the active ester curing agent is 1-30 parts by weight, for example, 1 part by weight, 4 parts by weight, 10 parts by weight, 12 parts by weight, 18 parts by weight, 23 parts by weight, 26 parts by weight or 30 parts by weight.
[0033] In the present invention, the black halogen-free epoxy resin composition further comprises other inorganic fillers.
[0034] In the present invention, the other inorganic filler is selected from any one or a combination of at least two of aluminum hydroxide, silicon dioxide, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, montmorillonite, clay or mica.
[0035] Preferably, the median particle size of the inorganic filler is D50 = 1.1-2.8 μm (for example, 1.1 μm, 1.3 μm, 1.6 μm, 1.9 μm, 2.0 μm, 2.5 μm or 2.8 μm), and the maximum particle size is D100 = 4.0-12.0 μm (for example, 4.0 μm, 4.8 μm, 5.9 μm, 6.3 μm, 7.6 μm, 8.8 μm, 9.5 μm, 10.1 μm, 11.2 μm and 12.0 μm).
[0036] Preferably, the physical form of the inorganic filler may be flake, rod, sphere, hollow sphere, granule, fiber or plate.
[0037] In the present invention, relative to 100 parts by weight of the epoxy resin, the content of the other inorganic filler is 30-200 parts by weight, for example, 30 parts by weight, 60 parts by weight, 100 parts by weight, 130 parts by weight, 180 parts by weight or 200 parts by weight.
[0038] Preferably, the black halogen-free epoxy resin composition further comprises a phosphorus-containing flame retardant.
[0039] In the present invention, the phosphorus-containing flame retardant is selected from reactive phosphorus-containing flame retardants and / or additive phosphorus-containing flame retardants.
[0040] Preferably, the reactive phosphorus-containing flame retardant is a compound containing phosphorus element and a reactive group.
[0041] Preferably, the reactive groups include amino groups and / or phenolic hydroxyl groups.
[0042] Preferably, the reactive phosphorus-containing flame retardant comprises phosphorus-containing phenolic formaldehyde.
[0043] Preferably, the additive phosphorus-containing flame retardant includes any one of tri(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 2,6-di(2,6-dimethylphenyl)phosphinobenzene, 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, phosphazene compounds or phosphate esters, or a combination of at least two thereof.
[0044] In the present invention, relative to 100 parts by weight of epoxy resin, the additive phosphorus-containing flame retardant is added in an amount of 10-30 parts by weight, such as 10 parts by weight, 12 parts by weight, 15 parts by weight, 16 parts by weight, 18 parts by weight, 21 parts by weight, 24 parts by weight, 27 parts by weight or 30 parts by weight. The phosphorus-containing flame retardant can provide good dielectric properties and flame retardancy, but excessive addition will lead to the problem of increased thermal expansion coefficient.
[0045] In the present invention, the black halogen-free resin composition further comprises a curing accelerator.
[0046] Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
[0047] On the other hand, the present invention provides a resin adhesive solution, wherein the resin adhesive solution is obtained by dissolving or dispersing the above-mentioned black halogen-free resin composition in a solvent.
[0048] In another aspect, the present invention provides a prepreg, comprising the black halogen-free resin composition as described above.
[0049] Preferably, the prepreg comprises a base material and the above-mentioned black halogen-free resin composition attached to the base material.
[0050] Preferably, the prepreg comprises a base material and the above-mentioned black halogen-free resin composition attached to the base material after impregnation and drying.
[0051] In another aspect, the present invention provides a metal foil-clad laminate, comprising at least one prepreg as described above and a metal foil coated on one side or both sides of the laminated prepreg.
[0052] In another aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg as described above or the metal foil clad laminate as described above.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] In the present invention, by controlling the Na ion content of black silica and controlling the pH, the CAF resistance of the board is improved while ensuring the light shielding effect and fluidity, and the dielectric properties are further optimized, meeting the requirements of reliability and high-speed signal transmission during PCB application, and broadening the application field of black copper clad laminates. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] The materials and grades involved in the following examples and comparative examples are as follows:
[0057] A1: CNE type epoxy resin (o-cresol epoxy resin): NPCN-704, epoxy equivalent: 200-220g / eq, Nan Ya resin;
[0058] A2: NC3000H, biphenyl type epoxy resin, epoxy equivalent: 290-300g / eq, Nippon Kayaku;
[0059] A3: bisphenol A epoxy resin, KE-8128, equivalent weight: 185-190g / eq, KOLON, Korea;
[0060] B1: black silica, SE0067, pH 5.3, Na ion content 534ppm, D50: 2.5-3.0μm, no surface treatment, Suzhou Jinyi;
[0061] B2: black silica, pH 6.5, Na ion content 89ppm, D50: 2.2-2.8μm, treated with isocyanate-based silane coupling agent, homemade;
[0062] B3: black silica, SE009Z, pH 6.4, Na ion content 289ppm, D50: 3.8-4.4μm, no surface treatment, Suzhou Jinyi;
[0063] B4: black silica, pH 6.4, Na ion content 278ppm, D50: 3.8-4.4μm, treated with epoxy surface treatment agent, homemade;
[0064] B5: black silica, DQM5010, pH 7.6, Na ion content 226ppm, D50: 1.0-1.8μm, no surface treatment, Suzhou Jinyi;
[0065] B6: black silica, pH 8.5, Na ion content 198ppm, D50: 1.8-2.5μm, no surface treatment, homemade;
[0066] C1: styrene maleic anhydride copolymer: SMA-EF30, Cray Valley, USA;
[0067] C2: Active ester curing agent: DFE-617L, Sichuan Dongcai;
[0068] C3: bisphenol A benzoxazine, LZ8290, HUNSTMAN;
[0069] D1: Phosphorus-containing phenolic resin: XZ92741, Dow, USA;
[0070] D2: Phosphate flame retardant: PX200, Japan Daihachi;
[0071] E: Silica powder: DS2032A, D100 is 11μm, Jiangsu Lianrui;
[0072] F: Curing accelerator: 2-ethyl-4-methylimidazole, Shikoku Chemical.
[0073] Preparation example:
[0074] (1) Synthesis of B2 isocyanate-modified black silica
[0075] 5 kg of black silica NQL7030 was put into a high-speed mixing agitator, the equipment was heated to 110°C, a hydrolyzed mixed solution (30 g KBM-803, 30 g ethanol, 60 g pure water for hydrolysis for 30 min) was added, and the mixture was stirred for modification for 20 min to obtain black silica B2 with epoxy surface treatment.
[0076] (2) Synthesis of B4 epoxy-modified black silica
[0077] 5 kg of black silica SE009Z was put into a high-speed mixing agitator, the equipment was heated to 110°C, a hydrolyzed mixed solution (30 g KBM-403, 30 g ethanol, 60 g pure water for hydrolysis for 30 min) was added, and the mixture was stirred for modification for 20 min to obtain black silica B4 with epoxy surface treatment.
[0078] (3) Synthesis of B6 black silica
[0079] Take 1000g of deionized water at room temperature and put it into a reactor with a stirrer, turn on the stirring, and add 180g of methyltrimethoxysilane and a small amount of acetic acid by weight to adjust the pH to about 5. After the methyltrimethoxysilane is dissolved, add 80g of ammonia water with a volume concentration of 5% and stir for 10 seconds before stopping stirring. After standing for 1 hour, filter and dry to obtain spherical polysiloxane powder. Put the spherical polysiloxane powder into a muffle furnace, set the nitrogen flow rate to 300mL / min, and raise the temperature in the furnace to 850℃ at a rate of 5C / min in a nitrogen atmosphere. Keep warm for 10 hours, heat treat the particles so that the organic groups in the particles are thermally decomposed into carbon elements to obtain black silicon dioxide B6, which has a pH of 8.5, a Na ion content of 198ppm, and a D50 of 1.8-2.5μm.
[0080] The resin compositions provided in the examples and comparative examples were used to prepare laminates for printed circuits according to the following method, and the prepared laminates were tested for performance. The components of the resin composition and butanone were placed in a container, stirred evenly to form a glue, and the glue was adjusted with a solvent to form a glue solution with a solid content of 60%. 2116 electronic grade glass fiber cloth was impregnated with the glue solution and baked in an oven to form a prepreg;
[0081] The laminate is made by bonding 6 prepregs together by heating and pressurizing, and then covering the upper and lower surfaces with metal foils, and placing smooth steel plates and plastic pads outside the upper and lower metal foils, and pressing them in a laminator.
[0082] The lamination operation conditions are as follows: when the temperature is 80-140°C, the heating rate is controlled at 1.5-2.5°C / min; when the temperature of the outer layer material is 80-100°C, full pressure is applied; the full pressure is about 350psi; during curing, the material temperature is controlled at above 200°C and kept warm for more than 100 minutes.
[0083] The formulation composition and physical property data of each embodiment are shown in Table 1, and the formulation composition and physical property data of the comparative example are shown in Table 2.
[0084] Table 1
[0085]
[0086]
[0087] Table 2
[0089]
[0090] The performance test items and specific test methods are as follows:
[0091] (1) Glass transition temperature: Differential scanning calorimetry (DSC) is used to measure the glass transition temperature according to the DSC method specified in 2.4.25 of IPC-TM-650.
[0092] (2) Dielectric constant (10 GHz): Measured using the SPDR method in accordance with the method specified in 2.5.5.9 of IPC-TM-650.
[0093] (3) CTE-Z: measured using a thermomechanical analyzer in accordance with the method specified in IPC-TM-650 2.4.24.
[0094] (4) Surface resistivity: tested according to IPC-TM650 2.5.17.1;
[0095] (5) Volume resistivity: tested according to IPC-TM650 2.5.17.1;
[0096] (6) CAF resistance: tested according to IPC-TM650 2.6.25;
[0097] (7) Transmittance: Tested using a transmittance tester
[0098] (8) Water absorption rate: After etching the copper foil on the surface of the copper clad laminate, dry the substrate and weigh the original weight. Then place the substrate in a pressure cooker at 120°C and 150 kPa for two hours. Take it out and wipe it dry with a dry cloth. Weigh the weight of the sample after water absorption. The PCT water absorption rate is (weight after cooking - weight before cooking) / weight before cooking.
[0099] (9) T288: Use a thermomechanical analyzer and perform the measurement in accordance with the method specified in IPC-TM-650 2.4.24.1.
[0100] (10) Flammability: measured according to the vertical combustion method of UL-94 standard.
[0101] (11) PCT limit: After being treated at 85°C and 85% RH for 6 hours, the heat resistance limit at 288°C was tested.
[0102] (12) PP lack of resin: Observe the appearance of PP under strong light. ◎- indicates serious lack of resin; ○- indicates slight lack of resin; ×- indicates no lack of resin.
[0103] (13) Plate grooves: Observe the surface condition of the plate edge with naked eyes. ◎- indicates severe grooves; ○- indicates slight grooves; ×- indicates no grooves.
[0104] From the perspective of board performance, compared with Example 1, Comparative Example 1 does not add black silica, resulting in too high light transmittance of the board; compared with Example 1, Comparative Example 2 has a low pH value of black silica and a high Na ion content, resulting in a decrease in CAF resistance; compared with Example 1, Comparative Example 3 has a relatively high pH value of black silica, resulting in poor moisture and heat resistance and obvious CAF resistance degradation; compared with Example 1, Comparative Example 4 has a small amount of low-dielectric curing agent, resulting in obvious degradation of dielectric properties; compared with Example 1, Comparative Example 5 has a large amount of curing agent, resulting in poor compatibility; compared with Example 1, Comparative Example 6 has a relatively high light transmittance due to the small amount of black silica added; compared with Example 3, Comparative Example 7 has a reduced resistivity and a decreased CAF resistance due to the excessive amount of black silica used.
[0105] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the black halogen-free resin composition, the prepreg, the laminate and the printed circuit board containing the same, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the scope of protection and disclosure of the present invention.
Claims
1. A black halogen-free resin composition, characterized in that: The black halogen-free resin composition comprises the following components in parts by weight: (A) Epoxy resin: 100 parts (B) Black silica: 10-30 parts (C) Low dielectric curing agent: 30-100 parts The black silicon dioxide has a pH value of 6-8 and a sodium ion content of ≤300ppm.
2. The black halogen-free resin composition according to claim 1, characterized in that: The black silicon dioxide is treated with a silane surface treatment agent; Preferably, the silane surface treatment agent is selected from isocyanate silane surface treatment agents.
3. The black halogen-free resin composition according to claim 1 or 2, characterized in that: The particle size distribution D50 of the black silica is 1-5 μm, and D100 is 7-12 μm.
4. The black halogen-free resin composition according to any one of claims 1 to 3, characterized in that: The epoxy resin is selected from any one of a bifunctional epoxy resin or a multifunctional epoxy resin or a combination of at least two thereof; Preferably, the epoxy resin is selected from any one or a combination of at least two of dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethyl biphenyl epoxy resin, biphenyl epoxy resin, novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, epoxy resin containing C1-C6 alkyl, MDI modified epoxy resin, epoxy resin containing naphthalene ring or epoxidized polybutadiene; Preferably, the epoxy equivalent of the epoxy resin is 100 to 600 g / eq.
5. The black halogen-free resin composition according to any one of claims 1 to 4, characterized in that: The low dielectric curing agent is selected from one or a combination of at least two of an amine curing agent, a cyanate curing agent, an active ester curing agent, an anhydride curing agent or a maleimide curing agent; Preferably, the anhydride curing agent is selected from any one of the following formula I or formula II or a combination of at least two thereof: Wherein, n:x=1:1 to 8:1; Preferably, the active ester curing agent is selected from any one or a combination of at least two of the active esters having the following structure of Formula III or Formula IV: In III, X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25; In IV, m, n, and q are independently integers of 1 to 6, X is phenyl or naphthyl, and Y is the following group: Where K is 0 or 1; Preferably, the low dielectric curing agent comprises an active ester curing agent, and the content of the active ester curing agent is 1-30 parts by weight.
6. The black halogen-free resin composition according to any one of claims 1 to 5, characterized in that: The black halogen-free epoxy resin composition further comprises other inorganic fillers; Preferably, the other inorganic filler is selected from any one or a combination of at least two of aluminum hydroxide, silicon dioxide, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, montmorillonite, clay or mica; Preferably, the inorganic filler has a median particle size D50 = 1.1-2.8 μm and a maximum particle size D100 = 4.0-12.0 μm; Preferably, the physical form of the inorganic filler may be flake, rod, sphere, hollow sphere, granule, fiber or plate; Preferably, relative to 100 parts by weight of the epoxy resin, the content of the other inorganic filler is 30-200 parts by weight; Preferably, the black halogen-free epoxy resin composition further comprises a phosphorus-containing flame retardant; Preferably, the phosphorus-containing flame retardant is selected from reactive phosphorus-containing flame retardants and / or additive phosphorus-containing flame retardants; Preferably, the reactive phosphorus-containing flame retardant is a compound containing phosphorus element and reactive groups; Preferably, the reactive groups include amino groups and / or phenolic hydroxyl groups; Preferably, the reactive phosphorus-containing flame retardant comprises phosphorus-containing phenolic formaldehyde; Preferably, the additive phosphorus-containing flame retardant includes any one of tris(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 2,6-bis(2,6-dimethylphenyl)phosphinobenzene, 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, phosphazene compounds or phosphates, or a combination of at least two thereof; Preferably, the additive phosphorus-containing flame retardant is added in an amount of 10-30 parts by weight relative to 100 parts by weight of the epoxy resin; The black halogen-free resin composition further includes a curing accelerator; Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
7. A resin glue, characterized in that: The resin glue is obtained by dissolving or dispersing the black halogen-free resin composition according to any one of claims 1 to 6 in a solvent.
8. A prepreg, characterized in that: The prepreg comprises the black halogen-free resin composition according to any one of claims 1 to 8.
9. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate comprises at least one prepreg as claimed in claim 8 and a metal foil covering one side or both sides of the stacked prepreg.
10. A printed circuit board, characterized in that: The printed circuit board includes at least one of the prepreg according to claim 8 or the metal foil clad laminate according to claim 9.
Citation Information
Patent Citations
A black spherical silicon dioxide and its preparation method and black copper clad laminate
CN118125458B
Low coefficient of thermal expansion thermosetting resin composite, preimpregnated material and metal foil-clad plate
CN103360724A
Black photosensitive resin composition
CN108628096A
Black resin composition, prepreg and laminated board
CN111500016A
Resin composition for sealing semiconductor, semiconductor device made by using it, and method of manufacturing semiconductor
JP2002053733A